Crosstalk between keratinocytes and immune cells in inflammatory skin diseases - Xinhui Ni; Yuping Lai (Exploration of Immunology, 2021)
Cutaneous homeostasis is maintained by dynamic cellular communications between different cell types in the skin through interactions with various mediators, including cytokines, chemokines and antimicrobial peptides/proteins (AMPs). Keratinocytes, as the major cell type of the epidermis, not only form a passive physical barrier, but also actively participate in the pathogenesis of many, if not all, inflammatory skin diseases. Keratinocytes highly interact with immune cells to shape, amplify or regulate inflammatory responses, thus triggering and/or sustaining these inflammatory skin diseases. In this review, crosstalk between keratinocytes and immune cells is summarized, and its contributions to two major inflammatory skin disorders including psoriasis and atopic dermatitis are highlighted.